Management of a patient with frostbite - Heluszka, Jakub; Fussek-Styga, Urszula; Błaszczyk, Agnieszka; Trojan, Sara; Kwieciński, Jakub; Miszuda, Sławomir; Szwedkowicz, Agata; Basiaga, Bartosz; Bednarz, Krzysztof; Leśniak, Marek (Journal of Education, Health and Sport, 2023)
Introduction and purpose Frostbite is a serious injury caused by cold, which is an inseparable element of human contact with nature. It can cause tissue damage and loss of function if not properly treated. It treatment consists of several stages that require the involvement of many people. The purpose of the article is to summarize information on epidemiology, pathophysiology, prehospital and hospital procedures and to draw attention to the complexity of patient care. Materials and methods A literature review based on PubMed and Google Scholar using the following keywords: frostbite, cold injury. Description of the state of knowledge: The literature review shows the breadth of the issue. The effectiveness of therapy depends on: knowledge of pathophysiology and risk factors, early diagnosis, discontinuation of exposure to cold, effective analgesic treatment, fluid therapy, transport of the victim to the appropriate center, rapid warming of frozen tissues, imaging diagnostics, initiation of thrombolytic treatment and, if necessary, surgery. It is also important to remember about long-term complications that worsen the quality of life of patients, such as chronic pain, hyperaesthesia or impairment or loss of limb functionality. Conclusions Frostbite is a relatively rare problem, but especially in winter, every medic will have to deal with it sooner or later. Considering the above information, the management of a patient with frostbite is a demanding and long-term process in which the cooperation and involvement of many medics is important, so it is worth having knowledge about them.